2022
DOI: 10.3390/ijms23105821
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyles Shape the Cytochrome P450 Repertoire of the Bacterial Phylum Proteobacteria

Abstract: For the last six decades, cytochrome P450 monooxygenases (CYPs/P450s), heme thiolate proteins, have been under the spotlight due to their regio- and stereo-selective oxidation activities, which has led to the exploration of their applications in almost all known areas of biology. The availability of many genome sequences allows us to understand the evolution of P450s in different organisms, especially in the Bacteria domain. The phenomenon that “P450s play a key role in organisms’ adaptation vis a vis lifestyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Our study results strongly support previous studies that show that the transition from saprophytic to ectomycorrhizal lifestyle resulted in the loss of specific gene complements and enrichment of novel genes in Pezizomycetes, indicating genomelevel changes for adaptation [3,4]. This phenomenon seems universal as it was observed in bacteria [36,[53][54][55][56][57] and a few fungal species [35,37,38,43,58] where the transition from saprophytic to pathogenic or simple lifestyles resulted in the loss of P450s or the development of unique P450s. More fungal genomes from different fungal groups need to be investigated to obtain conclusive evidence on changes in P450 complements between saprotrophs and mycorrhizal lifestyle.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study results strongly support previous studies that show that the transition from saprophytic to ectomycorrhizal lifestyle resulted in the loss of specific gene complements and enrichment of novel genes in Pezizomycetes, indicating genomelevel changes for adaptation [3,4]. This phenomenon seems universal as it was observed in bacteria [36,[53][54][55][56][57] and a few fungal species [35,37,38,43,58] where the transition from saprophytic to pathogenic or simple lifestyles resulted in the loss of P450s or the development of unique P450s. More fungal genomes from different fungal groups need to be investigated to obtain conclusive evidence on changes in P450 complements between saprotrophs and mycorrhizal lifestyle.…”
Section: Discussionsupporting
confidence: 92%
“…Based on the analysis of bacterial P450s, authors have proposed that P450s play a crucial role in an organism’s adaptation vis-à-vis the lifestyle of organisms, which impacts the P450 content in their genome [ 36 ]. This phenomenon has also been reported with fungal P450s, in a few cases distinct P450 families and subfamilies bloomed (are present in many copies within the same species) to help fungi adapt to ecological niches [ 35 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the very recent study, Msweli et al selected species of the phylum Proteobacteria classes, Alpha, Beta, Gamma, Delta, and Epsilon. The study identified that the lifestyle of alpha‐, beta‐, gamma‐, delta‐, and epsilon‐proteobacterial species profoundly affected P450 profiles in their genomes (Msweli et al, 2022). P450s analysis in the ancient and diverse bacterial phylum Proteobacteria revealed that pathogenic species or species adapted to living on simple carbon sources lost or have fewer P450s than saprophytes or species with complex lifestyles.…”
Section: Microbial P450omesmentioning
confidence: 99%
“…Cytochrome P450 monooxygenases (CYPs/P450s) are a superfamily of heme-containing enzymes known for their broad substrate specificities and diverse catalytic activities. Genomic sequence analysis of P450s in Bacteria has shown that these enzymes are frequently located in operons and biosynthetic gene clusters (BGCs) [1][2][3][4], functioning as oxidative tailoring enzymes, leading to functional diversity in the generated secondary metabolites [5,6]. Due to their catalytic diversity with stereo-and regio-specific oxidation capabilities, P450 enzymes have been exploited for various applications, including biomedical and biotechnological applications [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…As of 2023, 1910 P450 families have been identified in Bacteria [14]. Among the Bacteria P450 families, the CYP107 family is found to be dominantly present in BGCs, such as in Streptomyces [15], Firmicutes [16], and Gamma-and Delta-proteobacteria [2], indicating key role(s) for CYP107 family members in the synthesis of many BGC-derived secondary metabolites. Streptomyces species produce two-thirds of all microbial-derived secondary metabolites, including antibiotics [17], and CYP107 is dominant in their BGCs [15].…”
Section: Introductionmentioning
confidence: 99%